Zoelham Hospital's Public Policy Strategy in Handing COVID-19 in Binjai City - M. Ramfauzan Simanjorang; Syahrul Abidin (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of this research is to determine the public policy strategy at RSUD Dzoelham Binjai. The urgency of this research stems from the widespread COVID-19, which is destroying the world order. Based on the issues, RSUD Dzoelham must implement a public policy that allows patients exposed to COVID-19 to recover and reduces the number of spreads. Using a descriptive qualitative methodology based on observation, interviews, and documentation, this article examines Dzoelham Hospital's public policy strategy in dealing with COVID-19 in Binjai City. The findings of this study indicate that the management of the Dzoelham Hospital follows the regulations of the Presidential Instruction through the Central Government and the Ministry of Health of the Republic of Indonesia by performing PCR tests on patients exposed to COVID-19. Dzoelham Hospital also provides outpatient and inpatient care and collaborates with other hospitals to maximize referrals.